ADMINISTRATIVE AND PHARMACEUTICAL SCREENING OF DIABETES MELLITUS PRESCRIPTIONS IN TYPE 2 DIABETES MELLITUS PATIENTS IN THE HOSPITAL X JEMBER. - Michael Nicoin DC Michael Nicoin DC; Shinta Mayasari (Indonesian Pharmacopeia Journal, 2025)
AbstractBackground: Pharmaceutical services are drug and clinical pharmacy services that enhance therapeutic effects and minimize the risk of medication errors. A form of pharmaceutical service is prescription screening. Prescription screening is a prescription review which is an activity of pharmacists in reviewing prescriptions which includes administration before the prescription is compounded. Another study conducted by Aryzki entitled "Administrative completeness of prescriptions carried out at Pharmacy X Banjarmasin in January, completeness of 0.26%, incompleteness with a percentage of 99.74% has not met according to PERMENKES number 73 of 2016 concerning pharmaceutical service standards. Objective: To identify the administrative and pharmaceutical screening of DM prescriptions for type 2 DM patients at X Jember Hospital. Methods: Descriptive research using observation method with a total of 125 samples by Random Sampling using the slovin formula. Results: overall administrative completeness is 100% complete written indicators, while most of the pharmaceutical completeness (60%) is incomplete of the five indicators identified as not written, namely the dosage form is still 56.8%, the dosage of the drug is still 91.2%, and overall 100%, the rules of use have not been written. Conclusion: From the total sample taken 125 prescriptions in the administrative aspect were all written completely for the pharmaceutical aspect most of them were not written completely, namely the indicators of drug dosage forms, drug dosages, and rules of use. Keyword : Skrining; Administrative; Phasmaceutical; Indicato